The Impact of Exclusive Talent Management Philosophy on Employee Engagement in ABC Company - Shahaan, Liediawaty; Febriansyah, Hary (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2024)
This study investigates the effects of exclusive talent management philosophies on employee engagement within Company ABC, a multinational private healthcare corporation. The research focuses on how talent management strategies influence employees' levels of engagement. Company ABC, facing significant business challenges due to its dominant exclusive talent management strategy, emphasizes external recruitment and the development of a small group of high-potential employees. This approach has led to a decline in morale, employee engagement, and perceptions of fairness, as employees feel undervalued and overlooked. Primary data were collected through surveys administered to 104 Company ABC employees, ranging from entry-level to junior managers. The study employs quantitative analysis to assess the relationship between the company's talent management philosophy and employee engagement levels. Pearson Correlation technique was used to analyze the data. Findings reveal a negative correlation between exclusive talent management and employee engagement, indicating that a focus on a small group of employees can lead to feelings of exclusion and decreased motivation across the workforce. The thesis concludes with recommendations for Company ABC to transition to a more inclusive talent management approach. It advocates policies ensuring fair and equal treatment, development opportunities for all employees, and a culture that values diversity and inclusion. These changes are expected to enhance overall engagement, satisfaction, and organizational performance, aligning talent management with long-term business success.